2019
DOI: 10.5888/pcd16.180155
|View full text |Cite
|
Sign up to set email alerts
|

Intervention to Improve Access to Fresh Fruits and Vegetables Among Arkansas Food Pantry Clients

Abstract: Food pantries serve millions of Americans, yet the nutritional quality of foods distributed has been poor. Policy, systems, and environmental (PSE) changes were implemented in 3 food pantries in northwest Arkansas with the aims of improving the nutritional quality of foods distributed and increasing distribution of fresh fruits and vegetables (FFVs). Between pre-intervention and 1 year follow-up, food pantry bag audits showed increases from 20,256.38 to 25,108.46 calories distributed per household (P = .009) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(41 citation statements)
references
References 6 publications
1
40
0
Order By: Relevance
“…These findings contribute to the literature on interventions to increase fruit and vegetable consumption among lowincome populations (Gans et al 2016;Long 2019;Young 2013). It was encouraging to observe that clients in the post- SWAP group selected a higher proportion of green fruits and vegetables and a lower proportion of red fruits and vegetables.…”
Section: Discussionsupporting
confidence: 61%
“…These findings contribute to the literature on interventions to increase fruit and vegetable consumption among lowincome populations (Gans et al 2016;Long 2019;Young 2013). It was encouraging to observe that clients in the post- SWAP group selected a higher proportion of green fruits and vegetables and a lower proportion of red fruits and vegetables.…”
Section: Discussionsupporting
confidence: 61%
“…Small-scale and localized research studies have also suggested that clients rely on food pantries for large portions of their food ( 14 , 15 ) over long periods of time ( 1 , 14 , 16 ). The persistent nature of food insecurity and the chronic food needs of clients have been identified by hunger relief agencies in their recent move away from the term “emergency food system,” prompting food pantries to adopt new policies and interventions to improve the healthfulness and client-centeredness of their services ( 4 , 14 , 17 21 ).…”
Section: Introductionmentioning
confidence: 99%
“…This study raises awareness of the crucial need for nutrition education programmes and practical advice targeted at lowincome groups, regarding how to purchase and prepare healthy nutritious meals on a limited budget, to complement the mix of foods received from the food pantry. Interventions targeted at food pantry participants have focused on improving the dietary quality of foods supplied to and obtained from the pantry (32)(33)(34) . However, findings from the present study indicate that pantry foods may, in fact, be contributing greater mean amounts of key nutrients compared with other sources.…”
Section: Discussionmentioning
confidence: 99%